The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/app10124222
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Different Approaches to Infer Local or Regional Contributions to PM2.5 Burdens in Graz, Austria

Abstract: In early 2017 high particulate matter (PM) levels were observed across mid-Europe, including Austria. Here we characterize PM pollution in the city of Graz during January to March 2017, a period with substantial exceedances (34 days) of the European Union (EU) PM10 short time limit value. This study evaluates whether the observed exceedances can be attributed to the accumulation of pollutants emitted by local sources or to a larger scale pollution episode including transport. The analyses are based on the rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This approach assumes a fixed emission ratio between a compound emitted from a certain source and a tracer from that source (Li et al 2021 ). Although the macro-tracer method has been extensively applied to estimate the contribution of BB to OC and PM concentrations (e.g., Galindo et al 2021 ; Kirchsteiger et al 2020 ; Stracquadanio et al 2019 ; Theodosi et al 2018 ), it is important to bear in mind that tracer emissions depend on multiple factors such as the type of biomass burned, moisture content, and combustion conditions, leading to uncertainty in the quantification of the real contribution of BB to aerosol levels. The protocol used to determine OC concentrations also adds uncertainty to estimates of the BB contribution since emission ratios are based on OC measurements.…”
Section: Resultsmentioning
confidence: 99%
“…This approach assumes a fixed emission ratio between a compound emitted from a certain source and a tracer from that source (Li et al 2021 ). Although the macro-tracer method has been extensively applied to estimate the contribution of BB to OC and PM concentrations (e.g., Galindo et al 2021 ; Kirchsteiger et al 2020 ; Stracquadanio et al 2019 ; Theodosi et al 2018 ), it is important to bear in mind that tracer emissions depend on multiple factors such as the type of biomass burned, moisture content, and combustion conditions, leading to uncertainty in the quantification of the real contribution of BB to aerosol levels. The protocol used to determine OC concentrations also adds uncertainty to estimates of the BB contribution since emission ratios are based on OC measurements.…”
Section: Resultsmentioning
confidence: 99%
“…This rather simple approach was used to have a first approximation to differentiate between local and regional sources during a period of high PM concentrations as explained in the prior section. Based on PM 10 concentrations determined at GDB and the background site Bockberg (BB), Kirchsteiger et al (2020) identified time periods affected by long range transport (i.e. days showing quite similar concentration between GDB and BB and mass ratios ≤1.5) and days dominated by an influence of local sources (mass ratio >2).…”
Section: Sample Selection and Classificationmentioning
confidence: 99%
“…All measurements were done in duplicates. To derive organic matter (OM) a conversion factor of 1.5 was applied (OM = 1.5*OC) (Kirchsteiger et al, 2020).…”
Section: Oc/ecmentioning
confidence: 99%
See 1 more Smart Citation